Methylphenidate Blocks Effort-Induced Depletion of Regulatory Control in Healthy Volunteers. (June 2014) - Sripada, Chandra; Kessler, Daniel; Jonides, John
A recent wave of studies—more than 100 conducted over the last decade—has shown that exerting effort at controlling impulses or behavioral tendencies leaves a person depleted and less able to engage in subsequent rounds of regulation. Regulatory depletion is thought to play an important role in everyday problems (e.g., excessive spending, overeating) as well as psychiatric conditions, but its neurophysiological basis is poorly understood. Using a placebo-controlled, double-blind design, we demonstrated that the psychostimulant methylphenidate (commonly known as Ritalin), a catecholamine reuptake blocker that increases dopamine and norepinephrine at the synaptic cleft, fully blocks effort-induced depletion of regulatory control. Spectral analysis of trial-by-trial reaction times revealed specificity of methylphenidate effects on regulatory depletion in the slow-4 frequency band. This band is associated with the operation of resting-state brain networks that produce mind wandering, which raises potential connections between our results and recent brain-network-based models of control over attention.